The mechanism for regulating the isometric contraction of masseter muscles is involved in determining the vertical dimension of occlusion - Tanaka, Yuto; Sato, Hajime; Toyoda, Hiroki; Saito, Mitsuru; Maeda, Yoshinobu; Kang, Youngnam (Journal of neurophysiology, 2023)
Since 1934, the vertical dimension of occlusion (VDO) in edentulous individuals has been anatomically determined mostly by referring to the resting jaw position. However, such a static method is not always accurate. Considering the dynamic nature of clenching/mastication, it is desirable to determine VDO dynamically. We demonstrate that VDO can be accurately determined by measuring masseter EMG during the voluntary isometric contraction of jaw-closing muscles exerted against the ramp load in the jaw-opening direction. We previously demonstrated that accurate regulation of isometric contraction (IC) of jaw-closing muscles to counteract the ramp load applied to the jaw in the jaw-opening direction is achieved through the calibration between the two sensations arising from muscle spindles (MSs) and periodontal mechanoreceptors (PMRs). However, it remains unclear whether this calibration mechanism accurately works at any jaw positions, i.e., any vertical dimensions of occlusion (VDO). In the present study, we examined the effects of altering VDO on the IC of the masseter muscles in complete dentulous and edentulous subjects. At a VDO higher than the original VDO (O-VDO), the root mean square (RMS) of masseter EMG activity increased more steeply with a load increase, resulting in an over-counteraction. The regression coefficient of the load-RMS relationship significantly increased as the VDO was increased, suggesting that the overestimation became more pronounced with the VDO increases. Consistently also in the edentulous subjects, at a higher VDO than the O-VDO, a steeper increase in the RMS emerged with a delay in response to the same ramp load whereas a similar steeper increase was seen surprisingly even at a lower VDO. Thus, the edentulous subjects displayed a delayed overestimation of the ramp load presumably due to less and slowly sensitive mucous membrane mechanoreceptor (MMR) in alveolar ridge compared with the PMR. Taken together, the accurate calibration between the two sensations arising from MSs and PMRs/MMRs can be done only at the O-VDO, suggesting that the O-VDO is the best calibration point for performing accurate IC. NEW & NOTEWORTHY Since 1934, the vertical dimension of occlusion (VDO) in edentulous individuals has been anatomically determined mostly by referring to the resting jaw position. However, such a static method is not always accurate. Considering the dynamic nature of clenching/mastication, it is desirable to determine VDO dynamically. We demonstrate that VDO can be accurately determined by measuring masseter EMG during the voluntary isometric contraction of jaw-closing muscles exerted against the ramp load in the jaw-opening direction.